1968
DOI: 10.1159/000458235
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Serum γ-Glutamyl Transpeptidase in Different Internal Diseases Studied by Starch Gel Electrophoresis and Sephadex Filtration

Abstract: Summary: γ-glutamyl transpeptidase of human serum studied by starch gel electrophoresis and Sephadex filtration is not homogenous. Excepting liver cirrhosis no distinct distribution pattern of activity specific to any hepatobiliary disease or other internal diseases were found. Studies of GGTP heterogeneity seems to be of no great clinical significance in the differential diagnosis of hepatic or extrahepatic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1970
1970
1988
1988

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 4 publications
(4 reference statements)
1
9
0
Order By: Relevance
“…The different results of others [10,13,16] might be explained by the formation of multiple molecular forms, as Orlowski and Szczeklik [16] suggested, or by the different methods of enzyme assay. Another possible explanation might be that non-specific y-GT activity was detected by some workers.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The different results of others [10,13,16] might be explained by the formation of multiple molecular forms, as Orlowski and Szczeklik [16] suggested, or by the different methods of enzyme assay. Another possible explanation might be that non-specific y-GT activity was detected by some workers.…”
Section: Discussionmentioning
confidence: 94%
“…Each peak was eluted with one of the three protein fractions: the highest y-GT activity was eluted with albumin. Kokot and Kuska [13], and Jacyszyn and Laursen [20] have also found three peaks: they reported that the highest one was eluted with the y-globulin fraction. As far as the other two peaks are con cerned, Kokot and K uska have found them in the second, Jacyszyn and Laursen before the first protein fraction.…”
mentioning
confidence: 96%
“…2 show that only 47% of the enzyme activity is present at pH 9'0, the conditions employed by Jacyszyn and Laursen (1968). Several authors agree with a pH of 7·4 (Kulhanek and Dimov, 1966;Orlowski and Szezeklik, 1967;Kokot and Kuska, 1968), but it is worth noting that one of the advocates of pH 9·0 (Orlowski and Szewczuk, 1962) did not use glycylglycine as the acceptor substrate. While the pH optimum may rise in the absence of glycylglycine the value of an acceptor substrate is clearly demonstrated in Fig.…”
Section: Discussionmentioning
confidence: 95%
“…With these techniques conflicting reports have appeared on the number of isoenzymes to be found in the serum (Orlowski and Szczeklik, 1967;Rutenburg et 01., 1967;Jacyszyn and Laursen, 1968;Kokot and Kuska, 1968;Rosalki et al, 1970;Miyazaki and Okumura, 1972;Hetland et al, 1975). This confusion has arisen partly because different localisation techniques have been employed resulting in variations in sensitivity.…”
mentioning
confidence: 99%
“…also been shown by gel filtration [6,7,9,10,16]. However, the properties of the enzyme fractions which can be separated by these means and their relationship to each other and to tissue y-glutamyltransferase have not been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%